Self-consistent hybridization expansions for static properties of the Anderson impurity model - Hamad, Ignacio Javier (2015)
Building an effective Hamiltonian utilizing a projector-operatorprocedure, we derive an approximation based on a selfconsistenthybridization expansion to study the ground stateproperties of the Anderson Impurity model.We applied the approximationto the general case of finite Coulomb repulsionU, extending previous work with the same formalism in theinfinite-U case. The ground state energy and their related zerotemperature properties are accurately obtained in the case inwhich U is large enough, but still finite, as compared with the rest of energy scales involved in the model. The results for thevalence of the impurity are compared with exact results thatwe obtain from equations derived using the Bethe ansatz andwith a perturbative approach. The magnetization and magneticsusceptibility is also compared with Bethe ansatz results. Inorder to do this comparison, we also show how to regularizethe Bethe ansatz integral equations necessary to calculate theimpurity valence, for arbitrary values of the parameters.